Kinetics of IFN-gamma, TNF-alpha, IL-10 and IL-4 production by mononuclear cells stimulated with gp43 peptides, in patients cured of paracoccidioidomycosis - Sadahiro,Aya (2007)
We analyzed the kinetics of cytokine production by mononuclear cells from 17 patients who had been treated for paracoccidioidomycosis, using the stimulus of gp43 peptide groups (43kDa glycoprotein of Paracoccidioides brasiliensis) at 0.1 and 1µM, gp43 (1µg/ml) and crude Paracoccidioides brasiliensis antigen (PbAg; 75µg/ml). IFN-gamma production was a maximum at 144 hours in relation to the G2 and G8 peptide groups at 1µM and was greatest at 144 hours when stimulated by gp43 and by PbAg. The maximum TNF-alpha production was at 144 hours for the G2 group (0.1µM) and for gp43. IL-10 production was highest after 48 and 72 hours for G7 and G6 at 1µM, respectively. We also suggest the best time for analysis of IL4 production. These results may contribute towards future studies with gp43 peptides and encourage further investigations with the aim of understanding the influence of these peptides on the production of inflammatory and regulatory cytokines.